2016
DOI: 10.1002/jsid.417
|View full text |Cite
|
Sign up to set email alerts
|

KANSEI evaluation of color images presented in color gamuts with different blue primaries

Abstract: -The effect of blue primary color on image quality was studied. We used the KANSEI evaluation method, and for experiments, we used Semantic Differential method. First, four different blue primaries of 430, 450, 470, and 480 nm with full brightness of L max equal 60 cd/m 2 were tested.The same experiment was performed for 450, 470, and 480 nm at L max of 170 cd/m 2 . The results for the four primaries show that 450-and 470-nm blue primaries are the best. Then 430 nm was next, and 480-nm blue primary shows the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…Then allowable variability range of primaries along the spectral locus is also important. However, no study has been reported to examine the effect of gamut change using different color primaries along the spectral locus but ours [6]. In the previous study, we examined the effect of different monochromatic blue primaries, 430nm, 450nm, 470nm, and 480nm, at low luminance level (around 60 cd/m 2 ), and 450nm, 450nm, and 570nm at high luminance level (around 170 cd/m 2 ).…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Then allowable variability range of primaries along the spectral locus is also important. However, no study has been reported to examine the effect of gamut change using different color primaries along the spectral locus but ours [6]. In the previous study, we examined the effect of different monochromatic blue primaries, 430nm, 450nm, 470nm, and 480nm, at low luminance level (around 60 cd/m 2 ), and 450nm, 450nm, and 570nm at high luminance level (around 170 cd/m 2 ).…”
Section: Introductionmentioning
confidence: 90%
“…Test images, apparatus, evaluation words, and procedure are common to Exp.1 and Exp.2. Details of Exp.1 are described in Ayama et al [6].…”
Section: Common Parts To Experiments 1 Andmentioning
confidence: 99%
“…Example of "blue" image and the percentage of pixel distribution are shown in Figure 2. This image was used as a "blue" test image in the KANSEI evaluation study [9]. Ten images that were not classified into any of the 15 groups were added to test images.…”
Section: Methodsmentioning
confidence: 99%
“…First, we used the criteria indicated in Table 1 in the color classification. This was done originally for selecting proper color images that represent typical colors in the KANSEI evaluation experiment [9]. Fifteen color categories, red, green, blue,yellow, orange, red-green, green-blue, yellow-blue, yellowgreen,red-blue, pink, purple, multi-colors, monochromatic, and skin were employed.…”
Section: Initial Color Classificationmentioning
confidence: 99%
See 1 more Smart Citation